Academic Well-being among University Students - Attia, Arwa Rushdi; Muhammad, Zubaida Abbas (Journal of Tikrit University for Humanities, 2025)
The current research aims to identify the level of academic well-being among university students and the statistical differences according to the variables of gender and specialization. To achieve the objectives of the research, the researcher built a scale to measure academic well-being, consisting of 38 items in the final form, and each item has five alternatives: (Always applies to me - Often applies to me - Sometimes applies to me - Rarely applies to me - Never applies to me), As for the research sample, it consisted of 300 male and female students who were tested using a stratified random method from the faculties and departments of Tikrit University and using statistical methods. Validity, discrimination and reliability were verified using the following statistical methods (chi-square, Cronbach equation, t-test for one sample, t-test for two independent samples), and after processing the data statistically using the SPSS statistical package. The results showed the following: - Postgraduate students enjoy a high level of academic well-being. - There are no statistically significant differences according to the variables (gender - specialization). In light of the research results, the researcher came up with a number of recommendations and proposals